The Effect of Work Discipline, Work Motivation and Work Ethic on Private Employee Performance in Bandar Lampung - Candra, Ade; Ahadis, Hamartoni (Jurnal Mebis, 2025)
Abstract. This study aims to examine the effect of work discipline, work motivation, and work ethic on the performance of private employees in Bandar Lampung. The population of this research consists of private employees in Bandar Lampung, with a sample size of 140 employees. The sampling technique used is purposive sampling, based on Hair's formula (2017). The data analysis methods applied include multiple linear regression analysis, the coefficient of determination (R²), t-test, and F-test. The results of the study indicate that the variables of work discipline, work motivation, and work ethic each have a positive and significant influence on the performance of private employees in Bandar Lampung.